2011
DOI: 10.1177/147323001103900303
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Human Papillomavirus (hrHPV)-Associated Genes in Early Stage Cervical Squamous Cell Carcinomas

Abstract: This retrospective study investigated gene expression in tumour samples from 38 patients with early stage human papillomavirus (HPV)-associated cervical squamous cell carcinoma (CSCC). The patients were divided into two groups based on the presence of viral markers of HPV16 or HPV18 infection. Gene expression profiles of tumour samples and the corresponding normal cervical epithelium were analysed using cDNA microarrays. Several genes showed differential expression between the two groups of HPV-infected CSCC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…5,26 Because a gradual absence of IL-1A was also found in cervical tissue sections, inactivation of IL-1A signaling apparently inhibits its central role in the balance between inflammation and antiviral immunity against an HPV infection, thereby significantly contributing to the development of cervical cancer. 27 On the basis of the previously mentioned information, we suggested that IL-1AY511C/T polymorphism could be involved in cervical cancer pathogenesis and may be a potential relevant factor for cervical cancer by affecting IL-1 production or altering levels of IL-1 gene expression.…”
Section: Discussionmentioning
confidence: 84%
“…5,26 Because a gradual absence of IL-1A was also found in cervical tissue sections, inactivation of IL-1A signaling apparently inhibits its central role in the balance between inflammation and antiviral immunity against an HPV infection, thereby significantly contributing to the development of cervical cancer. 27 On the basis of the previously mentioned information, we suggested that IL-1AY511C/T polymorphism could be involved in cervical cancer pathogenesis and may be a potential relevant factor for cervical cancer by affecting IL-1 production or altering levels of IL-1 gene expression.…”
Section: Discussionmentioning
confidence: 84%
“…Other authors also recommend the use of at least two reference genes for human tissues [43], [44]. However, even though it has been widely accepted that one of the best ways to normalize the qPCR data is to use at least 2 to 3 reference genes, several studies of cervical cancer continue to use the most well-known reference genes such as GAPDH [23], [45], ACTB [30], EEF1A1 [46] and RNU6 [15], [24][27], [46][51], as a single reference gene and without mentioning whether this stage has been performed accurately. Furthermore, even though it has been established that a normalization standard must reflect the quantity and size of the target of interest to obtain comparable samples [12], [22]; some studies have used an mRNA as a reference gene to normalize the miRNA expression levels in cervical cancer [25], [51].…”
Section: Discussionmentioning
confidence: 99%
“…These cells are important sensors of pathogens and danger signals that mediate immune responses, supporting the notion that keratinocytes, which are the main target of HPV infection, also have to be considered as central nonprofessional immune competent cells of the mucosa [10], [31]. Although IL-1β was recently identified to be targeted by high-risk HPV as a central hub within the network of innate immunity [5] and down-regulated in cervical tumors [32]–[34], our knowledge about its function and regulation in the context of HPV-induced carcinogenesis is still rudimentary.…”
Section: Introductionmentioning
confidence: 99%